The chaos machine : the inside story of how social media rewired our minds and our world - Fisher, Max (New York : Little, Brown and Company, 2022)
"We all have a vague sense that social media is bad for our minds, for our children, and for our democracies. But the truth is that its reach and impact run far deeper than we have understood. Building on years of international reporting, Max Fisher tells the gripping and galling inside story of how Facebook, Twitter, YouTube, and other social networks preyed on psychological frailties to create the algorithms that drive everyday users to extreme opinions and, increasingly, extreme actions. As Fisher demonstrates, the companies' founding tenets, combined with a blinkered focus on maximizing engagement, have led to a destabilized world for everyone." -- Front jacket flap. Prologue: Consequences -- Trapped in the casino -- Everything is Gamergate -- Opening the portal -- Tyranny of cousins -- Awakening the machine -- The fun house mirror -- The germs and the wind -- Church bells -- The rabbit hole -- The new overlords -- Dictatorship of the like -- Infodemic -- Epilogue: Whistleblowing. "We all have a vague sense that social media is bad for our minds, for our children, and for our democracies. But the truth is that its reach and impact run far deeper than we have understood. Building on years of international reporting, Max Fisher tells the gripping and galling inside story of how Facebook, Twitter, YouTube, and other social networks preyed on psychological frailties to create the algorithms that drive everyday users to extreme opinions and, increasingly, extreme actions. As Fisher demonstrates, the companies' founding tenets, combined with a blinkered focus on maximizing engagement, have led to a destabilized world for everyone." -- Front jacket flap.